Persepsi Kebahagiaan Pada Masyarakat Banjar di Desa Gandaraya Kecamatan Anjir Pasar Kabupaten Barito Kuala - Rahmawati, Rahmawati; Arni, Arni; Imadduddin, Imadduddin (Jurnal Al-Husna, 2020)
Happiness is a feeling that can be experienced by everyone, but the way to get happiness varies depending on how the person perceives it. The purpose of this research is to find out how the level and perception of happiness in the Banjar community. This type of research uses a mixed method with 55 people for a quantitative approach and 12 people for a qualitative approach taken from a sample of 55 people who have high levels of happiness. Data collection techniques used were, questionnaire, observation and interview.  The results of this study can be concluded that the level of happiness of adolescents with high happiness categories is 35% and moderate 65%, adults are high happiness categories 55% and moderate 45%, and elderly happiness categories are high 46.7% and moderate 53.3%. Perceptions of happiness in adolescents are positive emotions, gratitude, family, achievement, peers, and social life. Adults are positive emotions, be patient and grateful, family, marriage, physical health, money, work, social life, and religiosity. While the elderly are positive emotions, gratitude, age, money, family, physical health, religion, social life.